Exit Surveys Assessment of Bachelor Mechanical Engineering Programs at Universiti Malaysia Pahang - M. S. M., Sani; M. M., Noor; K., Kadirgama; M. R. M., Rejab; M. M., Rahman; M. Y., Taib (2009)
Continuous improvement is an ongoing effort to improve products, services or processes. These efforts can seek “incremental” improvement over time or “breakthrough” improvement all at once. This paper explores the assessment of exit surveys to assess the graduate students of Faculty of Mechanical Engineering (FKM), Universiti Malaysia Pahang. The exit survey was covered the student’s impressions towards teaching and learning, skills and knowledge related to Program Outcomes (PO’s), student ratings for lecturer’s contributions, student opinions towards academic resources and overall graduate preparation by FKM. The outcome of assessment processes and how it can be facilitate to improve the mechanical engineering program was also investigated. The survey was conducted during last academic semester (first semester of the year 2008/2009). It is observed that all program outcomes have at least 70% student rating towards skills and knowledge preparation related to the program outcomes. This is confirmed outcome based education strategies when the entire curriculum should mapping to the program outcomes. Based on this survey, approximately more that 76.8% of the respondents are agreed that the mechanical engineering program are suitable and recommended of study to community.